EFL TEACHERS’ OF AUTHENTIC WRITING ASSESSMENT PRACTICES IN TEACHING VHS STUDENTS - Rahmat, Abiadi (Borneo Journal of English Language Education, 2019)
Indonesian Minister of Education and Culture regulations no. 66 of 2013 on National Educational Assessment Standards suggests that authentic assessment practices be employed in performing learning assessment in schools. However, former Minister of MONE reveals that many teachers find this a great challenge to them (Kompas.com, 2014). This study explores VHS EFL teachers? authentic writing assessment practices in their classrooms. Twenty EFL marketing teachers from nine VHS in East Jakarta have been involved as respondents for the study. A set of questionnaires for teacher respondents, a checklist for analysis of their lesson-plans, and semi-structured interviews for teacher respective students have been employed to collect data for the study. Discussion on findings of the study will be aimed at mapping the observed authentic writing assessment practices of the target respondents. The data obtained from teachers? questionnaire, students? interview and checklist document analysis, it can be concluded that EFL teachers from nine different vocational schools in teaching marketing students practice authentic assessment for assessing students? output. The type that teachers chose is intensive. It means teachers concern with students? vocabulary and grammar. Then the technique that they provide for assessing students? writing is essay.?